Chord box : poems - Rogers, Elizabeth Lindsey, 1985- (University of Arkansas Press, 2013)
These poems were written by a poet raised in North Carolina and educated at Oberlin College and Cornell University. She also spent several years in rural China, where she taught English and dance.